Effects of 4-week small-sided games vs. high-intensity interval training with changes of direction in female collegiate basketball players - Zeng, J.; Xu, J.; Xu, Y.; Zhou, W.; Xu, F. (International Journal of Sports Science & Coaching, 2022)
The aim of the study was to investigate the effects of 4-week small-sided games (SSG) and high-intensity interval training with changes of direction (HIT-COD) on physical performance and specific technical skills in female collegiate basketball players. Nineteen players were divided into SSG (n = 9) and HIT-COD (n = 10) groups, that performed either SSG or HIT-COD three times per week for 4 weeks during the pre-season. Players heart rate (HR) and perceived exertion responses (RPE) were assessed during the intervention. Before and after the intervention period, performances were assessed with 30-15 intermittent fitness test (30-15IFT), repeated sprint ability (RSA) test, modified agility T-test (MAT), countermovement jump (CMJ), 20-m sprint, shooting accuracy test, 1 min shooting test, passing test, defensive movement test and control dribble test. Both training interventions led to similar physiological and perceived exertion responses, showing no significant differences in HR (P = .49, d = 0.2) and RPE (P = .77, d = 0.1) between groups. Significant improvements were observed in 30-15IFT (SSG: 4.1%, d = 1.5; HIT-COD: 4.2%, d = 1.7), RSAmean (SSG: 2.2%, d = 1.0; HIT-COD: 1.9%, d = 1.0), RSAbest (SSG: 2.0%, d = 0.9; HIT-COD: 2.1%, d = 1.1), MAT (SSG: 7.2%, d = 1.7; HIT-COD: 5.7%, d = 1.5), defensive movement test (SSG: 5.1%, d = 2.1; HIT-COD: 5.8%, d = 1.8) and control dribble test (SSG: 3.4%, d = 1.0; HIT-COD: 2.6%, d = 1.0). The only significant group time interaction was found (P = .032, p2 = 0.24), with SSG improving 1 min shooting (22.4%, d = 1.0) and HIT-COD performing slightly worse ( 2.6%, d = 0.1) after a 4-week intervention.The current study suggests that using SSG is more effective than HIT-COD for female collegiate basketball players in pre-season, since SSG improves physical performance and basketball-specific movements as well as shooting abilities after a 4-week intervention.